The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1017/s1461145710001604
|View full text |Cite
|
Sign up to set email alerts
|

The serotonin transporter availability in untreated early-onset and late-onset patients with obsessive–compulsive disorder

Abstract: The pathogenetic role of central serotonin transporters (SERT) in obsessive-compulsive disorder (OCD) has been investigated in vivo by positron emission tomography (PET) or single-photon emission computed tomography (SPECT) studies with inconsistent results. This might reflect methodological differences but possibly also the pathophysiological heterogeneity of the disorder, i.e. the age at onset of OCD. The aim of our study was to compare SERT availability in patients with OCD to healthy controls (HC) taking i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 55 publications
4
34
0
Order By: Relevance
“…Other studies suggested SERT to be implicated in OCD (Hesse et al 2011;Simpson et al 2003) and substance abuse (Brown et al 2007), especially MDMA (McCann et al 2005Selvaraj et al 2009). SERT has further been linked to obesity and Parkinson's disease (e.g., Wang et al 2010a).…”
Section: Transportersmentioning
confidence: 99%
“…Other studies suggested SERT to be implicated in OCD (Hesse et al 2011;Simpson et al 2003) and substance abuse (Brown et al 2007), especially MDMA (McCann et al 2005Selvaraj et al 2009). SERT has further been linked to obesity and Parkinson's disease (e.g., Wang et al 2010a).…”
Section: Transportersmentioning
confidence: 99%
“…Notably, genetic susceptibility effects are mediated by molecular and cellular mechanisms, which in turn modulate behavioral phenotypes by affecting the structural and functional properties of neural circuits (Atmaca et al, 2011;Hesse et al, 2011;MacMaster, 2010;Wu et al, 2012). Therefore, such translational studies that implement genetics and imaging techniques may reveal the etiology of OCD more precisely (MacMaster, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical and pharmacological studies found that selective serotonin reuptake inhibitors (SSRIs), which facilitate serotonin neurotransmission, are effective choices for medical treatments of OCD (Geller et al, 2003;Goddard et al, 2008). OCD patients also showed abnormally reduced serotonin transporter availability in limbic and paralimbic brain areas, especially in the late-onset OCD patients (Hasselbalch et al, 2007;Hesse et al, 2011). Not all studies, however, found this pattern of results.…”
Section: Discussionmentioning
confidence: 99%
“…SLC6A4 is also the molecular target of selective serotonin reuptake inhibitors (SSRIs), the most clinically effective medications for OCD treatment (APA, 2007;Geller et al, 2003;Goddard et al, 2008). Brain imaging studies have also suggested that late-onset OCD, but not the earlyonset OCD, is associated with abnormally low serotonin transporter availability in the brain (Hasselbalch et al, 2007;Hesse et al, 2011). Therefore, the SLC6A4 gene is an ideal candidate gene for research on OCD/OCS.…”
mentioning
confidence: 99%